PENGARUH KONSENTRASI ASAP CAIR BERBASIS TEMPURUNG KELAPA DAN CANGKANG KELAPA SAWIT TERHADAP KARAKTERISTIK LATEKS YANG DIGUMPALKAN - Bareta, Arief; Purwanto, Heri; Giyanto, Giyanto (Institut Teknologi Sawit Indonesia (ITSI), 2021)
Liquid smoke is the result of the coconut shell pyrolysis and palm kernel shells burned and cooled through the medium of water coolers to make the results from burning fuel to liquid. Liquid smoke can be used to agglutinate latex. In this research, liquid smoke from coconut shell and oil palm shells mixed into 20gr of latex samples with a concentration ratio of 3%, 6%, 9%, 12%, and 15%. In this study, it can be concluded that the concentration of 15% faster agglomerate, lower pH, and higher PoPRI value. And faster agglomeration speed of other rubber materials.